The role of the endocannabinoid system in managing neuropsychiatric symptoms in Alzheimer’s disease - Rao, Jagadeesh S.; Alejandra Tangarife, Maria; Venegas, Maria Margarita; Forero, Barbara; González Tamayo, Laura Lucía; Escobar-Gallego, Juan Pablo; Rodríguez-Soacha, Diego A.; Ferreiros, Alexandra; Mukunda, Ram (Frontiers in Psychiatry, 2026)
The endocannabinoid system comprises cannabinoid receptors (CBRs) 1 & 2, endocannabinoids (eCBs) anandamide (AEA) and 2-arachidonoylglycerol (2-AG), and the enzymes that regulate their production and degradation. ECS plays a significant role in both health and disease. It influences neuronal and glial communications, neurotransmitter regulations, neuroinflammation, and behavioral alterations. Neuropsychiatric symptoms (NPS) are commonly seen in neurodegenerative conditions like Alzheimer’s disease (AD), apart from the core clinical diagnosis of dementia. NPS consists of various disturbing symptoms, including anxiety, agitation, apathy, hallucinations, delusions, sleeping problems, appetite problems, and depression. In AD, up to 97% exhibit one or more NPS. Emerging evidence from preclinical and clinical studies suggests that ECS is both a contributor to and a potential therapeutic target for managing NPS. This review explores ECS’s role in NPS and its therapeutic implications.